High-throughput bioprinting of spheroids for scalable tissue fabrication - Myoung Hwan Kim; Yogendra Pratap Singh; Nazmiye Celik; Miji Yeo; Elias Rizk; Daniel J. Hayes; Ibrahim T. Ozbolat (Nature Communications)
Abstract Tissue biofabrication mimicking organ-specific architecture and function requires physiologically-relevant cell densities. Bioprinting using spheroids can achieve this, but is limited due to the lack of practical, scalable techniques. This study presents HITS-Bio (High-throughput Integrated Tissue Fabrication System for Bioprinting), a multiarray bioprinting technique for rapidly positioning multiple spheroids simultaneously using a digitally-controlled nozzle array (DCNA). HITS-Bio achieves an unprecedented speed, ten times faster compared to existing techniques while maintaining high cell viability ( > 90%). The utility of HITS-Bio was exemplified in multiple applications, including intraoperative bioprinting with microRNA transfected human adipose-derived stem cell spheroids for calvarial bone regeneration ( ~ 30 mm3) in a rat model achieving a near-complete defect closure (bone coverage area of ~ 91% in 3 weeks and ~96% in 6 weeks). Additionally, the successful fabrication of scalable cartilage constructs (1 cm3) containing ~600 chondrogenic spheroids highlights its high-throughput efficiency (under 40 min per construct) and potential for repairing volumetric defects.